2010
DOI: 10.1093/eurpub/ckp241
|View full text |Cite
|
Sign up to set email alerts
|

Violence during pregnancy and newborn outcomes: a cohort study in a disadvantaged population in Brazil

Abstract: In disadvantaged settings in Brazil, violence in pregnancy is frequent; it is associated with inadequate maternal weight gain during pregnancy and prenatal care, and increases risk of low birth-weight. Thus, violence in pregnancy imposes a challenge to effective prenatal care delivery with potential benefits to the mother and her baby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
3
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 27 publications
9
57
3
18
Order By: Relevance
“…However, studies have shown an association between IPV and increased risk of abortion, increased risk of preterm delivery, association of violence with increased risk of stillbirth and perinatal death (22)(23)(24) . In another study, no statistically significant association between planned pregnancy and IPV, as well as a study conducted in Mexico found no association between the number of prenatal visits and the occurrence of IPV (25)(26) , agreeing with the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, studies have shown an association between IPV and increased risk of abortion, increased risk of preterm delivery, association of violence with increased risk of stillbirth and perinatal death (22)(23)(24) . In another study, no statistically significant association between planned pregnancy and IPV, as well as a study conducted in Mexico found no association between the number of prenatal visits and the occurrence of IPV (25)(26) , agreeing with the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Also with respect to the type of labor, it has not been verified in the literature association with IPV (26) .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Publications in English, French, German, Portuguese, and Spanish were potentially considered for the review. Exclusion criteria were: (1) studies on sexual aggression/rape in mixed samples of children, adolescents, and adults, where it was unfeasible to separate victimization of adults, adolescents, and children (except for two studies that included pregnant women older than 13 years 21,22 ); (2) when rates of sexual aggression were presented in combination with other forms of aggression (e.g., physical and psychological), thus preventing the separate identification of rates of sexual aggression individually; and (3) studies on sexual harassment, forced marriage or cohabitation, forced abortion, genital mutilation, obligatory inspection for virginity, forced prostitution, and sex trafficking. According to the World Health Organization (WHO), the latter terms fall under the broad definition of sexual violence 8 .…”
Section: Methodsmentioning
confidence: 99%
“…A 6% prevalence was found in a study conducted in the United States by the University of Texas with 16,041 women (37). In Latin America, the lowest prevalence (18.3%) was found in a hospital study conducted with 672 women from southern Brazil (38), while the highest (44.4%) was found in a study with 163 hospitalized women from Arica, Chile (39).…”
Section: An Approach Around Prevalence Data For Ipv During Pregnancymentioning
confidence: 99%